Making Health Care Reform Work: Where Physician and Employer Interests Converge - Allen, Harris; Nobel, Jeremy J; Burton, Wayne N (JAMA : the journal of the American Medical Association, 2012)
Fortunately, the Affordable Care Act's (ACA) emphasis on measurement, if broadened in a new direction, offers a path that will benefit both stakeholder groups in the current reform environment. This path should bring new empowerment to employers and thereby advance the staying power of ACA's reforms. If well managed, it would also yield a major collateral benefit for physicians--better measures of the value of their care for the outcomes-oriented compensation schemes mandated by the ACA. Here, Allen et al provide several examples that illustrate missed opportunities for strengthening employer linkages vis-a-vis the ACA.